Hubungan Pengetahuan dengan Kepatuhan Penerapan Perilaku Pencegahan Infeksi pada Keluarga Pasien di Ruang Rawat Inap RSUD Dr. R. Goeteng Taroenadibrata - Novia Niken Dwipayana; Ridlwan Kamaluddin; Arif Imam Hidayat (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
The patient's family has an important role in the implementation of infection prevention efforts in the hospital because of frequent contact with patients and susceptible to the entry of microorganisms. This behavior can be influenced by the knowledge factor. Individual behavior in accordance with applicable rules describes the extent to which the individual's level of compliance in implementing infection prevention behavior in the hospital. This study uses a cross sectional method with a total sample of 70 people taken by consecutive sampling technique. Collecting data using a questionnaire. The results of the Somers'd test showed that there was a significant relationship between knowledge and adherence to infection prevention behavior (p = 0.000).